Bahasa Indonesia - Choerunisa, Adelia Hasna (Widya Cakra: Journal of Psychology and Humanities, 2021)
Purchase intention is a tendency for personal action in the form of a conscious plan to buy a product. Interest is achieved by the existence of motivation in it which is driven by attention. Someone's attention arises because of an impression. In the digital era, online marketing uses celebrity endorsers to reach consumer attention. A celebrity endorser is expected to have the trustworthiness, expertise, and attractiveness to increase purchase intention. This study uses quantitative methods to determine the role of trustworthiness, expertise, and attractiveness of celebrity endorsers on the purchase intention of Instagram users during the Covid-19 pandemic. The subjects in this study were 371 Instagram users aged 18-34 years through incidental sampling. The measuring instruments of this research include the Purchase intention Scale, Trustworthiness Scale, Expertise Scale, and Attractiveness Scale. The results of the multiple regression test showed that trustworthiness, expertise, and attractiveness together have a significant role in the purchase intention of Instagram users.